SOCIAL MEDIA AND TEENAGE PSYCHOLOGY: THE IMPACT OF THE VIRTUAL WORLD ON YOUTH LIFE (International journal of artificial intelligence, 2024)
This article examines the influence of modern social media on teenage psychology through a comprehensive literature review. The analysis explores both positive and negative impacts of social networks on teenagers' lives, emphasizing the importance of balanced social media usage and discussing the role of parents and educators in guiding teens through digital engagement.